KINERJA USAHA MIKRO KECIL DAN MENENGAH DI KOTA AMBON BERDASARKAN LITERASI KEUANGAN - Stenly Jacobus Ferdinandus; Muspida Muspida (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aimed to empirically test and directly analyze how financial literacy affects the performance of MSMEs in Ambon City. This is verificative research, namely, testing the hypothesis through a quantitative approach. The unit of analysis used was all MSMEs in Ambon City. The purposive sampling technique was used to determine the number of samples, which obtained a sample of 96 MSMEs. The respondents of this study were the managers of MSMEs. This study used primary and secondary data, then processed using Partial Least Square (PLS). The results verificatively indicated that financial literacy, which consists of basic knowledge of financial management, savings and loans, insurance, and investment, partially affected the financial performance of MSMEs in Ambon City, positively and significantly. The results also indicated that the better the skills and knowledge of financial management, the better the performance improvement of MSMEs in Ambon City. The value of the coefficient of determination (R-Square) was obtained based on the test results, that is, 62.7% of MSME performance could be explained by financial literacy.